Saberes docentes e tecnologias digitais a partir da plataforma Google for Education no Instituto Federal de Sergipe - Andrade, Carla da Conceição (2019)
This research searches to understand which are the knowledge of the professionals who work as teachers in the Instituto Federal de Educação, Ciência e Tecnologia de Sergipe, and how they are built, to the use of the Digital Information and Communication Technologies (DICT) through the Google For Education platform. This is a qualitative investigation, of exploratory feature and that uses case studies as methodological strategies. The research is reasoned on the concepts of knowledge of Teachers and Digital Information and Communication Technologies (DICT). The scenery is the Instituto Federal de Educação, Ciência e Tecnologia de Sergipe – Tobias Barreto’s Campus. The sample is composed by two teachers selected in an intentional and non-probabilistic manner, besides an institutional management representative. The following evidences’ sources are used: Online and offline observation, institutional documents and interviews. The analysis of the sources result in three categories: Conception of DICT, teaching knowledge for the uses of the DICT and challenges about the DICT. The results show that the teachers understand the DICT as teaching support tools. Google For Education platform is known as the repository of contents discussed in the classroom. About the teaching knowledge for the uses of DICT, these are built in the ongoing formation, offered by the institute and in the acquired experience with classroom-based experience. The knowledge used by teachers are operational, turned to the functioning of the platform. Nevertheless, the teachers start to realize the pedagogic potential, playing it as a space of interaction among students or as support in the evaluative process.